IMPLEMENTATION OF THE OPERATIONAL CURRICULUM OF SEKOLAH PENGGERAK PROGRAM AT ELEMENTARY SCHOOLS - Saidah, Karimatus; Imron, Ilmawati Fahmi (PEDAGOGIK : JURNAL PENDIDIKAN, 2022)
The operational curriculum of Sekolah Penggerak program is part of the Sekolah Penggerak program that the Ministry of Education and Culture has launched. In this curriculum, there are changes in the curriculum structure that impact the preparation of learning plans and the implementation of learning activities in the classroom. Thus, this study aims to determine the perspective of teachers and school principals on the functional curriculum of the Sekolah Penggerak Program, the form of learning planning prepared by the teacher, and the implementation of learning activities in the classroom. The research method used is a qualitative method with data analysis techniques by Miles and Huberman. The results showed that teachers and principals welcomed the operational curriculum of the Sekolah Penggerak Program because it opened up creative space for teachers and schools to develop curriculum according to school needs. Meanwhile, there are formats and terms with the 2013 curriculum in preparing learning plans. Learning activities are carried out separately between subjects in the practical aspect of learning. There is no visible learning innovation because learning activities are limited, so the teacher focuses on strengthening the material.